RECONSTRUCTION THE PATTERNS OF AUTHORITY RELATIONS BETWEEN HEAD OF LOCAL GOVERNMENT AND SECRETARY OF LOCAL GOVERNMENT ON PROMOTION OF CIVIL SERVANTS - Tedi Sudrajat; Zainal Muttaqin (Jurnal Dinamika Hukum, 2016)
The pattern of the authority relation between head of local government and Secretary of local government in the promotion of Civil Servants lead into two pattern which are sub-ordination and coordination. Normatively, the position of Secretary is subordinate from Head of local government. Meanwhile, the pattern of coordination is a tiered pattern that puts Secretary as officials who provide recommendations of official candidate to Head of local government as the Trustees of the Local Employment Officer.Both of these relation creates superior position of Head of local government in the terms of promotion of civil servants. To create a proportional authority relation, it necessary pre-requisite form of commitment, orientation of human resources and the use of technology. On that basis, a mechanism must be created to limit the authority of the Head of local government by strengthening the system of merit-based technology.Keywords : position, authority, promotion of civil servants